Anterolateralni utesnitveni sindrom gležnja - Žnidaršič, Marta (Medicinski razgledi, 2011)
lnversion injuries of the ankle are common and most are managed adequately by functional treatment. A significant number will, however, remain symptomatic. Ankle impingement syndrome is clinicaly evident as pain, which is elicited by full range of motion in ankle joint because of the mechanical impidgement in the joint. Ankle impingement can result from trauma, infection, inflammation or from degenerative process. The impingement syndrome can be anterolateral, anteromedial, posterior, made of soft tissue or bone. This condition is of tendifficult to diagnose because the physical signs and investigations are non-specific. The presenting complaint is the pain with activities of daily living after an inversion ankle injury that has not resolved. The patient may note some mild swel1ing when comparing this ankle to the contralateral ankle. There may be a feeling of instability. Physical examination reveals localized palpable tendemess at the anterolateral comer of the ankle joint. Pain is of ten elicited by pasive forceful dorsiflexion of the ankle. The cardinal physical sign is the Molloy-Bendall impingement test. Most patients have no specific findings visible on medical imaging. Definitive diagnosis is made only with arthroscopy, which is therapeutic and diagnostic.
Keywords: Ankle Injuries; Sklep, bolezni; Skočni sklep zgornji; Arthroscopy; Ankle Joint; Gleženj, poškodbe; Joint Diseases; Artroskopija; Compartment Syndromes; Utesnitveni sindromi; gleženj; utesnitveni sindrom; zdravljenje; therapy